Analysis of Volleyball Service Learning Outcomes Through Inclusive Teaching Style (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2022)
This study aims to determine the improvement of volleyball bottom service learning outcomes for students of class XI MIPA II SMA Yayasan Pendidikan Mulia in the 2022/2023 academic year, through the application of inclusive teaching styles. The method used in this research is Classroom Action Research. The research was carried out in one cycle, which consisted of planning, implementing actions, observing and reflecting. To obtain data in this study, a learning outcome test was conducted at the end of the cycle in the form of an application for the lower service technique assessment. The data analysis technique used in this research is descriptively based on qualitative analysis with percentages. The results of the study conclude: (1) from the first cycle of learning outcomes tests obtained as many as 22 students with scores after being converted (88%) have reached the level of mastery learning , while 3 students (12%) have not reached the level of complete learning. With the average value of overall learning outcomes is 75.92. Based on the results of data analysis, it can be said that the application of inclusive teaching styles can improve the process of lower service learning outcomes for students of Class XI MIPA II SMA Yayasan Pendidikan Mulia in the Academic Year 2022/2023.